1986
DOI: 10.1002/mus.880090102
|View full text |Cite
|
Sign up to set email alerts
|

A morphological/biochemical study on the actions of corticosteroids on rat skeletal muscle

Abstract: Four corticosteroid hormones were administered (5 mg/kg/day) to rats over 6 to 10 days. Both biochemical and microscopic techniques were employed to determine the influence of these corticosteroids on the fine structure and growth of five striated muscles. Throughout, dexamethasone and triamcinalone were more potent than prednisone or cortisone in influencing muscle growth. The corticosteroids' action on the heart was anabolic, increasing its RNA and protein content. In contrast, the same corticosteroids were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
0
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 20 publications
8
44
0
1
Order By: Relevance
“…The reduced r2it.e of protein synthesis appeared to be due to a markedly reduced population of ribosomes; the efficiency oftranslation by the remaining ribosomes was not significantly altered from normal. The techniques employed by Kelly et al 12 could not determine the rate of synthesis or degradation of specific myofibrillar proteins, but the excellent preservation of the myofibrillar ultrastructure of the atrophic fibers would not be consistent with a selective or preferential loss of a major myofibrillar component.…”
Section: Discussionmentioning
confidence: 98%
“…The reduced r2it.e of protein synthesis appeared to be due to a markedly reduced population of ribosomes; the efficiency oftranslation by the remaining ribosomes was not significantly altered from normal. The techniques employed by Kelly et al 12 could not determine the rate of synthesis or degradation of specific myofibrillar proteins, but the excellent preservation of the myofibrillar ultrastructure of the atrophic fibers would not be consistent with a selective or preferential loss of a major myofibrillar component.…”
Section: Discussionmentioning
confidence: 98%
“…Corticosteroids differentially influence the rates of synthesis and/or breakdown of MHC isoforms [31]. The number of cortisol-specific and nonspecific receptors varies according to fiber type [16,20]. Type I fibers are partially protected by their greater contractile and/or oxidative activity [11,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The number of cortisol-specific and nonspecific receptors varies according to fiber type [16,20]. Type I fibers are partially protected by their greater contractile and/or oxidative activity [11,12,15,16]. Corticosteroid-induced inhibition of glucose uptake may have a greater affect on glycolytic fibers (IIb) than oxidative fibers (type I and IIa).…”
Section: Discussionmentioning
confidence: 99%
“…As in human disease, steroid myopathy has been induced in a variety of experimental animals using a number of different steroids. The fluorinated steroids, e.g., triamcinolone, betamethasone, and dexamethasone, appear more likely to produce steroid myopathy (4,5). Necrotic lesions are easily induced in the rat soleus muscle by steroid administration (4).…”
Section: Discussionmentioning
confidence: 99%
“…Although any of the commonly available glucocorticoid preparations can cause myopathy, the fluorinated steroids, e.g., triamcinolone, betamethasone, and dexamethasone, seem more likely to produce muscle weakness. The typical findings of steroid myopathy are selective atrophy of type II muscle fibers and necrotic changes (4,5). It has been suggested that glucocorticoid-induced mitochondrial damage can lead to muscle fiber necrosis (4,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%